PENGARUH MODEL PEMBELAJARAN AKUNTANSI BERBASIS PROBLEM TERHADAP PENINGKATAN SOFTSKILLS MAHASISWA JURUSAN AKUNTANSI PADA PTN DAN PTS DI KOTA AMBON - Jefry 0000000 Gasperz (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2015)
This study aims to investigate the influence of Problem-Based Learning/PBL) to increase student’s softskills in Accounting Department at Ambon City and then simultaneously generate accounting learning model that can be used by universities to improve the quality of learning both personal qualities and scientific quality through analytical skills, creativity, and open to innovation and new findings. The population in this study were students from the Department of Accounting at the Faculty of Economics and Faculty of Economics, Pattimura University in Darussalam Ambon. Samples were students from the Department of Accounting that would taken courses in Management Accounting at Department of Accounting - FE Pattimura University, and Darussalam University in Ambon City. In every department, sampling of 30 people. The sampling technique used is nonprobability sampling with purposive sampling. Methods of data collection begins with the class treatments (to make small groups, giving the case/problem, advice by the facilitator, discussion in small group, resume small group, and facilitators make conclusions on the problems discussed), then a questionnaire distributed to respondents for answering that how perception’s respondent of PBL influence to increase in student’s softskills. The results of hypothesis testing with simple regression analysis showed that problem-based learning (PBL) to have significant effect on the increase student’s softskill in university of state and university of private at Ambon City. Key Words: Problem-Based Learning, Softskills